The Tree, the Compass, and the Mirror: Toward a Sacred Philosophy of History in Sarawak - Mohd. Shazani, Masri (UNIMAS Online Journal System, 2025)
This article proposes a sacred philosophy of history grounded in Sarawak’s political memory, symbols, and contemplative traditions. In a post-truth era, where knowledge is frequently distilled into emotion, spectacle, and data, there is an imperative to restore significance in the study, remembrance, and dissemination of history. Guided by Tawhidic epistemology, this paper reimagines history not merely as a record of events, but as a field of signs and responsibilities that connect human life to higher truths. Through the metaphors of the tree (rooted memory), the compass (sacred tradition), and the mirror (collective reflection), it draws on the works of Sarawakian historians such as Sanib Said, Suffian Mansor, and Adibah Yusuf to show that a contemplative, spiritually grounded approach to history already exists within local traditions. The proposal resonates with the metaphysical insights of Muhammad Umar Faruque and responds to Jason Stanley’s critique of political knowledge in the post-truth era. By calling for the reintegration of the humanities and social sciences with science and technology, the article suggests that Sarawak’s unique historical consciousness may offer a path towards restoring meaning, dignity, and balance in education, leadership, and global civilisational discourse.